The Development of Mathematic Learning Using Virtual Reality Assisted by MilleaLab Application - Natasha Kirana; Kowiyah Kowiyah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This research is motivated by the finding that some students have difficulty understanding the concepts of LCM and GCF, because they have difficulty explaining the basics and distinguishing between LCM and GCF, which causes a decrease in learning motivation. Some students have not been able to explain the basic concepts well, and have difficulty in distinguishing between LCM and GCF, resulting in decreased learning motivation. Therefore, innovation in mathematics teaching methods is needed to make learning more interesting and effective. One solution is learning media facilitates students understanding through Virtual Reality technology. This research aims to produce Virtual Reality learning media that is valid, practical and appropriate for the MilleaLab Application. This research applies the ADDIE Research and Development (R&D) method. The research subjects were elementary school students from 2 classes: limited scale, and large scale. At each stage, referring to open media innovation in mathematics learning, the product was validated by experts who confirmed its suitability for students. Large-scale students response data showed a positive rate of 87,78% , classified as ‘’Good’’, indicating it can help students understand the material well. Trial data indicates that some students understand the functions and operation of Virtual Reality, but still required guidance in its use. Based on these result, it is recommended that an intensive and structured introduction and training in the use of Virtual Reality be provided. Ongoing mentoring is needed to ensure students fully understand the function and operation of Virtual Reality device, thereby maximizing their learning potential.